PELATIHAN PEMBUATAN ALAT PERAGA MATEMATIKA DAN IPA BAGI GURU-GURU SD ANA MARITIM SURABAYA - Ika Kurniasari; Affiati Oktaviarina; Dimas Avian Maulana (Universitas Negeri Surabaya, 2018)
In the cognitive development, students of elementary school need a real object in the learning process which has an impact on elementary school teachers who have to be able to make their own properties. The purpose of this community service is to provide information to teachers of SD Ana Maritim Surabaya to make the simple and easy media. Stages took in the process are: the participants formed a group of three and each group consists of three or four participants. Each group got the tools and materials needed to make props. Participants created props according to the directions available on given hand-out. The result of this community services are (1) the participants are making mathematical props using paper–coins integer and various forms of two-dimensional figure and (2) for Science media, participants created jumping can and coloured water in bottles.